MINAT BERWIRAUSAHA MAHASISWA BERDASARKAN TINGKAT KESEJAHTERAAN KELUARGA (STUDI KASUS DARI MAHASISWA UNIVERSITAS ISLAM DARUL ‘ULUM LAMONGAN) - Rifky Ardhana Kisno Saputra (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2019)
The welfare of the family is a family that is formed on the basis of legitimate marriage, able to meet the spiritual and material needs of life are worth , fear of God Almighty, have relationships which are harmonious , and balanced between family members and community members , as well as the environment. (Act No.10 of 1992 ). This study was included in the quantitative description of the type of research aims to test the hypothesis or not the relationship between the level of family welfare with interest in entrepreneurship students. Technique choose sample by simple random sampling that is by lottery. Methods of data collection in this study are questionnaires, interviews and documentation. Methods of analysis using correlation analysis technique using product moment formula.Based on the calculation of r xy was done to obtain the result of 0.77 indicates a strong correlation between variables X or higher and variable Y.